Modeling the Influence of Eutrophication and Redox Conditions on Mercury Cycling at the Sediment-Water Interface in the Berre Lagoon - Pakhomova, Svetlana; Yakushev, Evgeniy; Protsenko, Elizaveta; Rigaud, Sylvain; Cossa, Daniel; Knoery, Joel; Couture, Raoul-Marie; Radakovitch, Olivier; Yakubov, Shamil; Krzeminska, Dominika; Newton, Alice (Frontiers in Marine Science, 2018)
This study presents a specifically designed Mercury module in a coupled benthic-pelagic reactive-transport model - Bottom RedOx Model (BROM) that allows to study mercury (Hg) biogeochemistry under different conditions. This module considers the transformation of elemental mercury (Hg(0)), divalent mercury (Hg(II)) and methylmercury (MeHg). The behavior of mercury species in the model is interconnected with changes of oxygen, hydrogen sulphide, iron oxides, organic matter and biota. We simulated the transformation and transport of Hg species in the water column and upper sediment layer under five different scenarios, combining various levels of oxygenation and trophic state in the Berre lagoon, a shallow eutrophic lagoon of the French Mediterranean coast subjected to seasonal anoxia. The first scenario represents the conditions in the lagoon that are compared with experimental data. The four other scenarios were produced by varying the biological productivity, using low and high nutrient (N and P) concentrations, and by varying the redox conditions using different intensity of vertical mixing in the water column. The results of the simulation show that both oxidized and reduced sediments can accumulate Hg, but any shifts in redox conditions in bottom water and upper sediment layer lead to the release of Hg species into the water column. Eutrophication and/or restricted vertical mixing lead to reducing conditions and intensify MeHg formation in the sediment with periodic release to the water column. Oxygenation of an anoxic water body can lead to the appearance of Hg species in the water column and uptake by organisms, whereby Hg may enter into the food web. The comparison of studied scenarios shows that a well-oxygenated eutrophic system favors the conditions for Hg species bioaccumulation with a potential adverse effect on the ecosystem. The research is relevant to the UN Minimata convention, EU policies on water, environmental quality standards and Mercury in particular.